2017
DOI: 10.5530/jyp.2017.9.108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solanum nigrum Linn on Acute and Sub-Acute Models of Inflammation

Abstract: Objective: The aim of the study was to see the effect of ethanolic extract of Solanum nigrum Linn on Acute and Sub-acute inflammation. Method: Wistar rats weighing 150-200gms were used, divided into four groups Group 1 was control group, two groups Group 2 and 3 treated with the plant extracts at 100 & 200 mg/kg b.w and Group 4 treated with indomethacin, 10 mg/kg b.w. Acute inflammation was induced by injecting 0.1 mL of 1% homogenized carrageenan suspension in normal saline to the right hind paw of the rats p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…The NO production in S. nigrum fruit extract in 80% ethanol decreased to 4.1%, 16.1%, 61.0%, and 79.8% at concentrations of 0.125, 0.250, 0.500, and 1.000 mg/ml, respectively, and could also relieve edema and decrease the thickness of ear tissue in vivo , probably accounting for the abundance of alkaloid and flavonoid ( Yeom et al, 2019 ). Similar results in acute and subacute rat models, and the hydroalcoholic extracts of S. nigrum showed less deposition of macrophages and more deposition of collagen fibres and exhibited organ protection properties (liver, stomach, and kidney), perhaps owing to the presence of steroidal alkaloids and steroidal saponins of S. nigrum ( Aryaa and Viswanathswamy, 2017 ). Self-made S. nigrum suppository promoted the repair of damaged epithelial tissue and restored prostatic secretion through the decrease of the rat prostate wet quality and the white blood cell count and the increase in the density of lecithin corpuscle ( Xu et al, 2015 ).…”
Section: Pharmacological Activitiessupporting
confidence: 56%
“…The NO production in S. nigrum fruit extract in 80% ethanol decreased to 4.1%, 16.1%, 61.0%, and 79.8% at concentrations of 0.125, 0.250, 0.500, and 1.000 mg/ml, respectively, and could also relieve edema and decrease the thickness of ear tissue in vivo , probably accounting for the abundance of alkaloid and flavonoid ( Yeom et al, 2019 ). Similar results in acute and subacute rat models, and the hydroalcoholic extracts of S. nigrum showed less deposition of macrophages and more deposition of collagen fibres and exhibited organ protection properties (liver, stomach, and kidney), perhaps owing to the presence of steroidal alkaloids and steroidal saponins of S. nigrum ( Aryaa and Viswanathswamy, 2017 ). Self-made S. nigrum suppository promoted the repair of damaged epithelial tissue and restored prostatic secretion through the decrease of the rat prostate wet quality and the white blood cell count and the increase in the density of lecithin corpuscle ( Xu et al, 2015 ).…”
Section: Pharmacological Activitiessupporting
confidence: 56%
“…Solanum nigrum Linn is reported to have anti-inflammatory activity on both acute and sub-acute stages of inflammation. 17 Solanum melongena and Solanum macrocarpon extracts have shown inhibitory effect on NO production in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. 18 Phytoconstituents present in plants such as phenols, triterpenes, tannins, anthraquinones, and flavonoids may be responsible for these anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study performed at a dose of 375 mg/kg also indicated the anti-inflammatory action of plant berries [ 66 ]. At acute and sub-acute stages of inflammation, extract of the whole plant of S. nigrum (100 and 200 mg/kg) showed anti-inflammatory potential as compared to indomethacin (10 mg/kg)[ 69 ]. Ethanolic extract of the plant berries at 100, 200, and 300 mg/kg concentrations showed 28, 52, and 63% inhibition against carrageenan-induced paw edema.…”
Section: Solanum Nigrum In Covid-19 With Special Emphasis On...mentioning
confidence: 99%